Pengabdian Masyarakat Sebagai Tim Profesi Ahli Pada Penilaian Kesesuaian Dokumen Teknis PBG Lapangan Mini Soccer - Purwo Subekti; Bambang Edison; Anton Ariyanto; Taufik Kurniawan; Jhoni Rahman; Suganda (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the quality and technical compliance of Building Approval (Persetujuan Bangunan Gedung/PBG) documents through the involvement of a Professional Expert Team (Tim Profesi Ahli/TPA) in the development of a mini soccer field in Rambah Tengah Hilir Village, Rokan Hulu Regency, Riau Province, Indonesia. The activity was conducted as technical and regulatory assistance to PBG applicants to ensure that planning documents comply with applicable regulations and technical standards. The implementation adopted a participatory technical assistance approach, including technical document compliance assessment, regulatory and technical consultation, and collaborative validation through the Building Information Management System (SIMBG). The assessment comprehensively covered general data, architectural aspects, structural design, and mechanical, electrical, and plumbing (MEP) systems, referring to Government Regulation No. 16 of 2021, regulations of the Ministry of Public Works and Housing, and applicable Indonesian National Standards (SNI). The initial evaluation indicated that the documents were administratively complete; however, several technical non-compliances were identified, particularly in the structural and MEP aspects. Through continuous consultation and systematic revisions, all recommendations provided by the TPA were successfully addressed, resulting in full technical compliance and readiness for PBG approval.